THE PATTERN OF SKIN DISEASES OF PATIENTS ATTENDING THE OUT PATIENTS DEPARTMENT IN A MEDICAL COLLEGE IN A DISTRICT IN WEST BENGAL - NIRMALYA KUMAR DAS,; MOUSUMI ROY BANDYOPADHYAY,; DIBYENDU BASU,; PINKI BARDHAN,; SUCHIBRATA DAS,; SUJATA SINHA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study was to find out the pattern of skin diseases among the patients attending the Dermatology outdoor of a Medical College located in a district in West Bengal. Methods: This is an observational study. Patients attending the dermatology outdoor were included following the inclusion and exclusion criteria. Results: In this study, we found that infective diseases (51.09%) were more than non-infective diseases (44.31%). Among the infective diseases dermatophyte infection (15.22%) and Scabies (12.31%) were the highest. Eczema (11.68%) and contact dermatitis (10.07%) were the highest among the non-infective diseases. Conclusion: This study shows the pattern of skin diseases among the patients attending the dermatology outdoor. This gives a good idea about the skin diseases prevalent in this region. This knowledge will help to formulate policies regarding healthcare. It will also help to have an idea about the medicines and human resources required to deliver service to the people.